2000
DOI: 10.1111/j.1527-3458.2000.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Sipatrigine (BW 619C89) is a Neuroprotective Agent and a Sodium Channel and Calcium Channel Inhibitor

Abstract: Sipatrigine is a substituted pyrimidine derived from lamotrigine. It attenuates glutamate release in vitro and in vivo, probably as a result of sodium and calcium channel inhibition. It consistently reduces cortical infarct volume in rodent models of global, permanent focal, and transient focal ischemia (typically 50-60% reduction with maximum effective doses >20 mg/kg). Striatal protection was found in some studies but not others. The drug was effective also in a rat optic nerve model of white matter ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
(188 reference statements)
1
15
1
Order By: Relevance
“…Inward I Ca,L makes a significant contribution to the plateau phase of the AP 21 and it is therefore likely that partial block of I Ca,L by sipatrigine (IC = 50 −6 μmol/L) contributed to the shortening of APD 30 and, thereby, to the AP triangulation observed with higher concentrations of the drug. The IC 50 values for inhibition by sipatrigine of cardiac I Na (approximately 25 μmol/L) and I Ca,L (approximately 6 μmol/L) in the present study are very similar to those reported for native and recombinant neuronal voltage‐gated Na + (10–50 μmol/L) and various subtypes of Ca 2+ current, including L‐, N‐, P/Q‐, R‐ and T‐type currents (7–16 μmol/L) 1,22–29 . Thus, it can be concluded that sipatrigine shows little selectivity between cardiac and neuronal isoforms of Na + channel or between distinct Ca 2+ channel subtypes, further demonstrating its action as a broad‐spectrum cation channel blocker.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Inward I Ca,L makes a significant contribution to the plateau phase of the AP 21 and it is therefore likely that partial block of I Ca,L by sipatrigine (IC = 50 −6 μmol/L) contributed to the shortening of APD 30 and, thereby, to the AP triangulation observed with higher concentrations of the drug. The IC 50 values for inhibition by sipatrigine of cardiac I Na (approximately 25 μmol/L) and I Ca,L (approximately 6 μmol/L) in the present study are very similar to those reported for native and recombinant neuronal voltage‐gated Na + (10–50 μmol/L) and various subtypes of Ca 2+ current, including L‐, N‐, P/Q‐, R‐ and T‐type currents (7–16 μmol/L) 1,22–29 . Thus, it can be concluded that sipatrigine shows little selectivity between cardiac and neuronal isoforms of Na + channel or between distinct Ca 2+ channel subtypes, further demonstrating its action as a broad‐spectrum cation channel blocker.…”
Section: Discussionsupporting
confidence: 87%
“…Intriguingly, the corresponding regions in the IIIS6 and IVS6 domains of the cardiac L‐type Ca 2+ channel and the S6 domain of the cardiac I Kr hERG K + channel are also thought to play a role in drug binding, raising the possibility that sipatrigine may bind to similar regions of the channel pore‐forming α‐subunit of different classes of voltage‐gated cation channels 30,31 . Sipatrigine is highly lipid soluble 1 and the slow onset of current blockade by sipatrigine and the partial recovery on wash‐out of the drug observed for each of the currents in this study are consistent with a requirement for the drug to partition within the membrane for channel blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, structurally related agents, such as sipatrigine or 202W92 also exert inhibitory effects on Ca v 2.3 with IC 50 values of 10 mM (therapeutically relevant brain concentration: 20-100 mM (sipatrigine) and 56 mM (202W92). In addition, both sipatrigine and 202W92 are neuroprotective agents in animal models of ischemia (Caputi et al, 2001;Hainsworth et al, 2000) and interestingly, were shown to exert anticonvulsant effects in genetically epilepsy-prone rats and DBA/2 audiogenic mice (Hainsworth et al, 2003;Reddy et al, 1998).…”
Section: Article In Pressmentioning
confidence: 98%